A Ridge-to-Reef Ecosystem-Based Valuation Approach to Biodiversity Conservation in Layawan Watershed, Misamis Occidental, Philippines - Ureta, Julie Carl P.; Lasco, Rodel D.; Sajise, Asa Jose U.; Calderon, Margaret M. (2016)
Ecosystem services commonly valued by the society usually pertains to marketable ecosystem services while non-marketable ecosystem services, such as biodiversity, are usually left unaccounted for, making it less priority and beset with problems such as insufficient funding for conservation activities. Low appreciation on the economic value of these ecosystem services has led to overutilization, causing negative impacts to the environment. This study aimed to estimate the value of a non-marketable ecosystem service, biodiversity, through household’s willingness to pay for its conservation activity in Mt. Malindang Range Natural Park (MMRNP) Layawan Watershed. Similarly, a comparison between a “holistic” and “habitat-exclusive” management approaches was done to determine the best management strategy for implementing a sustainable financing mechanism. An average willingness to pay for R2R biodiversity conservation of PhP 43.58 (USD 0.90) per household per month for five years as compared to PhP 33.02 (USD 0.68) per month from an exclusive Upland ecosystem conservation approach and PhP 30.39 (USD 0.62) per month from an exclusive Coastal ecosystem conservation approach. Therefore, a Ridge-to-Reef approach on biodiversity conservation showed significantly higher willingness to pay from households as compared to habitat-based approach. The R2R approach could eventually generate PhP 7.5 M annually.
Keywords: Valuation